Adaptation Strategies for Sustaining the Economic Livelihood of Single-Parent Female Agricultural Labor in Nagari Koto Salak, Dharmasraya - Rara Aprilia Pramudita; Firdaus Firdaus; Elvawati Elvawati (LPPM Universitas PGRI Sumatera Barat, 2025)
This study examines the adaptation strategies of single-parent female farm labor in Nagari Koto Salak, Dharmasraya Regency, who face multiple social and economic challenges. With unstable incomes below the regional minimum wage, they are solely responsible for household needs, including daily consumption and children’s education, while constrained by low education levels, limited access to resources, and minimal social support. Using John W. Bennett’s (1976) framework of adaptation strategies—behavioral, tactical, and process—this research employs a descriptive qualitative approach. Data were collected through non-participant observation, in-depth interviews, and document analysis, involving eight main informants and eight supporting informants selected through purposive sampling. The findings reveal three key strategies: reducing consumption (behavioral), utilizing household resources, seasonal savings groups (arisan), income diversification, and borrowing (tactical), as well as participation in social groups such as dasawisma, religious study groups, and farmer groups (process). These strategies highlight the resilience and adaptive capacity of women in sustaining family livelihoods under vulnerable conditions.